"Dictionary of the Chuvash Language" by N.I. Ashmarin as a Guardian of the Genetic Memory of the People: Linguoculturological Aspect - Albina F. Myshkina; Inessa V. Iadranskaia (Развитие образования, 2020)
The article is devoted to identifying the role of the «Dictionary of the Chuvash language» by N.I. Ashmarin in revealing the mental foundations of modern Chuvash and in determining the sociocultural and psychological type of character of the Chuvash. The relevance of the study is due to the fact that during the period of globalization and universalization of cultures, the return to the original values of the nation, the search for individual-folk traits of a person's character in his worldview and lifestyle, which is most clearly recorded in his language, is of great importance. The human language retains a large amount of information that contributes to its spiritual, scientific, technical and industrial development. Therefore, the analysis of vocabulary also contributes to the study of the history of the development of man, people, nation, humanity. The purpose of the research is to study the socio-historical, cultural and ethical information enshrined in the vocabulary of the people and recorded in this dictionary. The principles of methodology, that reflect elements of conceptology, hermeneutics and general philology are used in the study. It is concluded that the Chuvash language (more broadly, the Chuvash culture) is an integral part of the ancient Turkic world, therefore research in this direction expands the framework of understanding the philosophy, history, theology and everyday life of the Chuvash people.